Intergenerational Actuarial Fairness when Longevity Increases: Amending the Retirement Age - Jorge Miguel Bravo; Mercedes Ayuso; Robert Holzmann; Edward Palmer (Center for Economic Studies and ifo Institute (CESifo), 2021)
Continuous longevity improvements and population ageing have led countries to modify national public pension schemes by increasing the standard and early retirement ages in a discretionary, scheduled, or automatic way, and by making it harder for people to retire prematurely. To this end, countries have adopted alternative retirement age strategies, but our analyses show that the measures taken are often poorly designed and consequently misaligned with the pension scheme's ultimate goals. In addition, our analyses demonstrate that countries risk falling short of their goals given their use of projection methods that underestimate life expectancy. This paper discusses how to implement automatic indexation of the retirement age to life expectancy developments while respecting the principles of intergenerational actuarial fairness and neutrality among generations. We show that in policy designs in which extended working lives translate into additional pension entitlements, the pension age must be automatically updated to keep the period in retirement constant. Alternatively, policy designs that pursue a fixed replacement rate are consistent with retirement age policies targeting a constant balance between active years in the workforce and years in retirement. The empirical strategy employed to project the relevant cohort life expectancy uses a Bayesian Model Ensemble approach to stochastic mortality modelling to generate forecasts of intergenerationally and actuarially fair pension ages for 23 countries and regions from 2000 to 2050. The empirical results show that the pension age increases needed to accommodate the effect of longevity developments on pay-as-you-go equilibrium and to reinstate equity between generations are sizeable and well beyond those employed and/or legislated in most countries. A new wave of pension reforms may be at the doorsteps.
Keywords: H55; G22; C63; C53; H23; 330; retirement age; actuarial fairness; intergenerational neutrality; pensions; Bayesian Model Ensemble; population ageing